2015
DOI: 10.1016/j.imr.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Water extract of Magnolia officinalis cortex inhibits osteoclastogenesis and bone resorption by downregulation of nuclear factor of activated T cells cytoplasmic 1

Abstract: BackgroundMagnolia officinalis cortex has been traditionally used to treat stomach and intestine diseases in traditional Korean medicine. In this study, we investigated the effect of water extract of M. officinalis cortex (WEMC) on osteoclast differentiation and function.MethodsPhytochemical characterization of WEMC was performed by high-performance liquid chromatography analysis. Osteoclast differentiation of bone marrow-derived macrophages was determined by tartrate-resistant acid phosphatase activity assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As bioactive polyphenolic compounds provide enormous health benefits with their antioxidant and anti-inflammatory properties [ 37 ], a new field of interest has emerged involving osteo-immune-oncology, bone metabolism, and tumorigenesis [ 5 , 6 , 9 , 12 , 38 ]. The data we have collected is in agreement with much of the previous literature on the interactions between polyphenolic compounds and osteoclastogenesis [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Antioxidant properties are well-studied for EA, GA, and TA [ 37 , 47 , 48 ], which is why we have chosen those molecules for the immune modulation of monocytes in our current study.…”
Section: Discussionsupporting
confidence: 90%
“…As bioactive polyphenolic compounds provide enormous health benefits with their antioxidant and anti-inflammatory properties [ 37 ], a new field of interest has emerged involving osteo-immune-oncology, bone metabolism, and tumorigenesis [ 5 , 6 , 9 , 12 , 38 ]. The data we have collected is in agreement with much of the previous literature on the interactions between polyphenolic compounds and osteoclastogenesis [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Antioxidant properties are well-studied for EA, GA, and TA [ 37 , 47 , 48 ], which is why we have chosen those molecules for the immune modulation of monocytes in our current study.…”
Section: Discussionsupporting
confidence: 90%
“…Recent finding has demonstrated that polyphenolic compounds inhibit receptor activator of nuclear factor- κ B ligand- (RANKL-) induced osteoclast formation [17]. Since the herbal congee containing the combination extract of P. odoratum and M. alba contained high concentration of polyphenol, this substance may possibly be active constituent which contributes a role on an antiosteoclastogenic effect of the herbal congee containing the combination extract of P. odoratum and M. alba .…”
Section: Discussionmentioning
confidence: 99%
“…However, a soluble decoy OPG produced by osteoblast binds to RANK, limiting excessive formation of mature osteoclasts ( Martin and Sims, 2015 ). A study showed that 2 inhibited osteoclast formation ( Li et al, 1998 ), and also prevented RANKL-induced osteoclast formation of bone marrow macrophages ( Shim et al, 2015 ). This is in agreement with our study, as our results showed that both 2 and 3 increased the mRNA expression level of OPG and subsequently decreased the level of RANKL, thus elevating the OPG/RANKL ratio ( Fig.…”
Section: Discussionmentioning
confidence: 99%